Studies in genetically modified mice implicate maternal HDL as a mediator of fetal growth. Issue 2 (4th January 2018) - Rebholz, Sandra L.; Melchior, John T.; Davidson, W. Sean; Jones, Helen N.; Welge, Jeffrey A.; Prentice, Andrew M.; Moore, Sophie E.; Woollett, Laura A.
Abstract : Studies in humans have shown a direct association between maternal plasma cholesterol concentrations and infant birthweight. Similarly, previous studies in our laboratory have shown that chow‐fed mice lacking apolipoprotein (apo) A‐I, the major protein in HDL, have low HDL‐cholesterol (HDL‐C) concentrations and smaller fetuses in midgestation. In the current study, we measured fetal weights in mice with varying levels of apoA‐I gene dose (knockout, wild‐type, and transgenic) and examined metabolic pathways known to affect fetal growth. As expected, we found the differences in apoA‐I expression led to changes in HDL particle size and protein cargo as well as plasma cholesterol concentrations. Fetal masses correlated directly with maternal plasma cholesterol and apoA‐I concentrations, but placental masses and histology did not differ between groups of mice. There was no significant difference in glucose or amino acid transport to the fetus or in expression levels of the glucose (glucose transporter 1 and 2) or amino acid (sodium‐coupled neutral amino acid transporter 1 and 2) transporters in whole placentas, although there was a trend for greater uptake of both nutrients in the whole fetal unit (fetus + placenta) of mice with greater apoA‐I levels; significant differences in transport rates occurred when mice without apoA‐I (knockout) vs. mice with apoA‐I (wild‐type and transgenic) were compared. Glucose tolerance tests were improved in the mice with the highest level of apoA‐I, suggesting increased insulin‐induced uptake of glucose by tissues of apoA‐I transgenic mice. Thus, maternal HDL is associated with fetal growth, an effect that is likely mediated by plasma cholesterol or other HDL‐cargo, including apolipoproteins or complement system proteins. A direct role of enhanced glucose and/or amino acid transport cannot be excluded.—Rebholz, S. L., Melchior, J. T., Davidson, W. S., Jones, H. N., Welge, J. A., Prentice, A. M., Moore, S. E., Woollett, L. A. Studies in genetically modified mice implicate maternal HDL as a mediator of fetal growth. FASEB J. 32, 717–727 (2018). www.fasebj.org